(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND /INTRODUCTION: Distal radius fractures (DRFs) are among the most common injuries treated in the Emergency Department (ED). A significant proportion of these fractures are displaced or angulated, requiring manipulation and reduction. Traditionally, this procedure is performed using intravenous (IV) procedural sedation and analgesia (PSA) or by giving hematoma block (HB). This study aims to evaluate the effectiveness of HB over IV-PSA, as it is less time-consuming, easier to administer, and more cost-effective. OBJECTIVE: The primary objective of this study is to compare the effectiveness of HB and IV-PSA in the reduction of DRFs. Efficacy is assessed by comparing the two methods in terms of average time taken to achieve adequate analgesia, changes in pain score during the procedure, ED LoS, adverse reactions, need for additional analgesia and overall outcome. MATERIAL AND METHODS: This is a quantitative prospective cohort comparative study involving 228 patients presenting to the ED with uncomplicated displaced DRF. Systematic nonprobability consecutive sampling was employed to recruit participants. The study participants were divided into two groups. The patients in Group A were administered HB while the patients in Group B received IV-PSA. Pain was recorded at various intervals before and after the procedure using the Visual Analog Scale (VAS). Outcomes of interest were average time taken to achieve adequate analgesia, delta change in pain score during the procedure, ED LoS, adverse reaction, need for further analgesia, and procedure success rate. RESULTS: Of the 228 patients, 109 (47.8%) were male and 119 (52.2%) were female. The mean age of the study participants was 38.16 ± 13.79 years, with ages ranging between 15 and 60 years. The mean pain score before treatment (VAS T1) was 5.29±2.25 in both groups. Thirty minutes after treatment (VAS T2), the median pain scores were 3 in the HB group and 4 in the IV PSA group, with a p-value of < 0.001, indicating statistical significance. The average time taken to achieve analgesia in the HB and IV-PSA groups was 10.2 min and 18.5 min, respectively. Seven patients required a second attempt at the HB, while nine patients needed a second attempt at IV-PSA. None of the patients in either group suffered from any adverse reactions. Procedure success rate was 95.48% and 88.31% In the HB and IV-PSA groups, respectively. CONCLUSION: Our study demonstrates that HB is more efficient than IV-PSA as quicker and long-lasting analgesia is achieved by this method. The ED LoS and rates of complication are also much lower. Procedure success rate is the same in both groups.